Relationship between ratio of 2nd and 4th digit lengths (2D:4D) and malocclusion in 13-15-years-old children: a case study at Unismuh Junior High School, Makassar - Ainnayah Lobud; Susilowati (Makassar Dental Journal PDGI Makassar, 2020)
Background: Malocclusion is a condition that is not in accordance with the process of growth and development that can be seen with the disharmony of the relationship between the teeth, relationship of jaw arches, face and overall. The 2D:4D ratio can be corelated with hormones that have a role in growth.Therefore, ratio 2D:4D can be used as an early marker of disease, intelligence, reproductive ability and probability of jaw growth patterns. Objective: To know the relationship between the ratio of second and fourth digit lengths (2D:4D) and the types of malocclusion on the students of Unismuh Junior HighSchool. Method: This observational descriptive study with purposive sampling was performed on students aged 13-15 years old with total sample 100 people.Malocclusion examination was conducted to identify the types of Angle and Dewey malocclusion. A digital vernier caliper was used to measure a ratio between2D and 4D. The data were analyzed using chi-square test. Result: 96 people had Class 1 (2D<4D=77, 2D>4D=19), 4 people had Class 2 (2D>4D=3, 2D<4D=1), Class 1 type 1 of 34 people (2D< 4D=29, 2D>4D=5), Class 1 type 2 of 3 people (2D<4D=2, 2D>4D=1) and Class 1 type 6 of 16 people (2D<4D=12,2D>4D=4). Conclusion: There was no relationship between the ratio 2D:4D with the types of Angle and Dewey malocclusion.